"Sluk så for det lort!" - Blaakilde, Anne Leonora (Tidsskrift for kulturforskning, 2017)
"Turn off that bullshit!" is the English translation of the Danish quote in the title, uttered by one of the interlocutors in this article. This folkloristic study of media culture consists of interviews with 14 Danish radio listeners born from 1928-1948. During their life course, the 14 interviewees have grown with media, learning to live a media life with radio as a phenomenon of sociability. The article focuses particularly on issues of negotiation and conflict while listeners are saturated in the soundscape of radio as a part of everyday life. The analysis of interactions between human/non-human actors involved in radio listening shows how the everyday life is influenced by the appearance of a media technology like radio, and how these actors, in a mutual process of "becoming", converge with wider cultural and social processes, such as the emergence of new cultural values related to "age", "family", "authorities", and "individual integrity". As a comment to Silverstone's notion of "domestication", referring to social groups, it is emphasized that listeners do not represent "one" listening culture in singularis, which is one reason why media use may result in conflicts among listeners who negotiate about the character of their common soundscape and imaginations of personal integrity that are trespassed by sounds from radio.